1986
DOI: 10.1515/semi.1986.58.1-2.107
|View full text |Cite
|
Sign up to set email alerts
|

Synesthesia: A principle for the relationship between the primary colors and the cardinal vowels

Abstract: A noir, E blanc, I rouge, U vert, O bleu: voyelles. Baudelaire, Le sonnet des voyelles Toute personne percevant une couleur eprouve la meme sensation et apprehende la meme qualite de vecu. C'est pourquoi la sensation que provoque la couleur est un langage sensible comprehensible partous sans recours au vocabulaire: un langage visuel. Luscher, 'Les couleurs sont des sentiments visualises'Synesthesia is, in rough terms, the spillover from one sense modality into another. An intense experience in one sense modali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Correspondence between red and /a/ is more difficult to explain. Perhaps formant structures play a role [16,17], yet a clear explanation remains to be provided. In experiment 1, a significant effect of the type of voice on color vowel matching was also found.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondence between red and /a/ is more difficult to explain. Perhaps formant structures play a role [16,17], yet a clear explanation remains to be provided. In experiment 1, a significant effect of the type of voice on color vowel matching was also found.…”
Section: Discussionmentioning
confidence: 99%
“…As chromaticity decreases (i.e., for high vowels), the importance of the light-dark contrast will be increased. Ryalls (1986) developed Jakobson's ideas further. He proposed that there was an organizing principle in the vowel-colour mapping: vowel "primes" ([i,a,u]) were associated with the "visual primes" (i.e., the primary colours yellow, red, and blue because all colours can be derived from these three colours), and he used such associations to derive hypothetical associations for other vowels.…”
Section: B Associations Between Vowels and Coloursmentioning
confidence: 99%
“…In addition, he suggested that the acute-grave (i.e., high front vs back) and diffuse-compact features of vowels parallel the chromatic (yellow-blue and green-red) and light-dark (white-black) contrasts of colours: acute-grave with yellow-blue; acute-grave with white-black; diffuse-compact with red-green. Ryalls (1986) proposed a perceptual link at the neurological level between the sense modalities of vision and hearing. Marks's (1975) meta-analysis of many case reports of coloured hearing revealed similar agreements across synaesthetes as also noted by Jakobson (1962) above: the vowel /a/ with red, /e/ and /i/ with yellow and white, /o/ with red and black, and /u/ with blue, brown, or black.…”
Section: B Associations Between Vowels and Coloursmentioning
confidence: 99%